IMPROVING THE ELEVENTH GRADE STUDENTS’ READING EXPOSITORY TEXT ACHIEVEMENT BY USING CRITICAL READING STRATEGY AT SMA PLUS NEGERI 4 OKU - NOVARITA NOVARITA (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this study were to find out (1) whether or not the usage of CriticalReading Strategy significantly improve the eleventh grade students’ readingexpository text achievement at SMA Negeri 4 OKU, (2) whether or not there issignificant difference in reading expository text achievement between the studentswho are taught by using Critical Reading Strategy and those who are taught by usingcommon strategy, (3) whether or not there is significant difference among theeleventh grade male students in reading expository text achievement who are taughtby using Critical Reading Strategy and those who are taught by using the commonstrategy, (4) whether or not there is significant difference among the eleventh gradefemale students in reading expository text achievement who are taught by usingCritical Reading Strategy and those who are taught by using the common strategy,(5) whether or not there is significant difference between the eleventh grade malestudents and female students in reading expository text achievement who are taughtby using Critical Reading Strategy, and (6) what The eleventh grade students’perception on the implementation of Critical Reading Strategy in their classroom.The population of this study covered all of the eleventh grade students of SMA N 4OKU in academic 2011/2012. The sample were selected using purposive randomsampling from the whole population. The writer chose fifteen male’s student andfemale’s students in experimental and control groups. The study was conducted inform of an experiment by doing 16 meetings of teaching including pre-test and posttest.During the research, the students in experimental group were taught readingmaterial by using critical reading strategy. The reading material were taken based onvalidity of the test. They are the levels of difficulty and the levels of appropriatenessof reading test items. To check whether the application of the instruction could runwell, the students were given reading comprehension tests. The obtained data wereanalyzed using t-test. The findings showed that there was a statistically significantprogress in the English reading achievement of the students who were taught byusing critical reading strategy. The questionnaire was used to find out the studentsperception on the implementation of critical reading strategy in their classroom. Theresults of t-test was used by the writer showed that there was significant different forall objective. In conclusion, Critical Reading Strategy was considered applicable toimprove reading expository text achievement at SMA Negeri 4 OKU.